Monitoring And Control System Of Industrial Electric Motors Using The Internet Of Things (IoT) - Irvan Hanafi; Fachrudin Hunaini; Diky Siswanto (Muhammadiyah University, Sidoarjo, 2023)
The electric motor plays an important role in an industry as a driver in a particular system, for example, rotating a pump impeller, fan or blower, moving a compressor, and lifting materials. The electric motor is sometimes called the